2021
DOI: 10.1016/j.infbeh.2021.101649
|View full text |Cite
|
Sign up to set email alerts
|

Associations between touchscreen exposure and hot and cool inhibitory control in 10-month-old infants

Abstract: Highlights No association between touchscreen exposure and inhibitory control at 10-months. Touchscreen exposure positively associated with Cognitive Executive Function score. Positive association found only after accounting for sociodemographic variables. Touchscreen exposure during infancy may be less detrimental than previously believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
2
14
1
1
Order By: Relevance
“…Results showed that 3.5-year-old children who had a higher level of touchscreen use showed poorer performance on a composite experimental measure of CF and WM, although these effects became non-significant after controlling for background TV. Our findings are broadly consistent with previous reports of EF difficulties related to television viewing ( Barr et al, 2010 ; Kostyrka-Allchorne et al, 2017a ; Lillard, Drell, et al, 2015 ; Lillard, Li, & Boguszewski, 2015 ; Lillard & Peterson, 2011 ) and media use ( Hendry et al, 2022 , McHarg et al, 2020 ); but contrast with a recent report of positive concurrent associations of touchscreen exposure and EFs at a much younger age (10 months), after controlling for sociodemographic variables ( Lui et al, 2021 ). Further, two recent studies, across a similar age period to our study, showed associations between mobile devices media use and IC, but no associations with WM or CF ( Lawrence et al, 2020 ; McNeill et al, 2019 ), while in our study we found no associations with a composite measure of impulse/self-control.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results showed that 3.5-year-old children who had a higher level of touchscreen use showed poorer performance on a composite experimental measure of CF and WM, although these effects became non-significant after controlling for background TV. Our findings are broadly consistent with previous reports of EF difficulties related to television viewing ( Barr et al, 2010 ; Kostyrka-Allchorne et al, 2017a ; Lillard, Drell, et al, 2015 ; Lillard, Li, & Boguszewski, 2015 ; Lillard & Peterson, 2011 ) and media use ( Hendry et al, 2022 , McHarg et al, 2020 ); but contrast with a recent report of positive concurrent associations of touchscreen exposure and EFs at a much younger age (10 months), after controlling for sociodemographic variables ( Lui et al, 2021 ). Further, two recent studies, across a similar age period to our study, showed associations between mobile devices media use and IC, but no associations with WM or CF ( Lawrence et al, 2020 ; McNeill et al, 2019 ), while in our study we found no associations with a composite measure of impulse/self-control.…”
Section: Discussionsupporting
confidence: 92%
“…If touchscreen use disrupts EF performance in pre-schoolers, as it has been shown before with TV and touchscreen media devices ( Barr et al, 2010 , Kostyrka-Allchorne et al, 2017b , Lawrence et al, 2020 , Lillard et al, 2015 , Lui et al, 2021 , McNeill et al, 2019 ) then we predict differences in all components of EF in children who have high daily touchscreen use compared to matched children with low daily touchscreen use, such that children with high daily touchscreen use will demonstrate worse EF performance compared to children with low daily touchscreen use.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Several longitudinal studies have found greater exposure to media and television in infancy and toddlerhood associates with worse cognitive outcomes later (Aishworiya et al, 2019 ; Christakis et al, 2004 ; Madigan et al, 2019 ; McHarg et al, 2020b ; Supanitayanon et al, 2020 ; Tomopoulos et al, 2010 ; Zimmerman & Christakis, 2005 ). Although positive concurrent associations between touchscreen use and cognitive EF have been observed among 10‐month‐olds (Lui et al, 2021 ), high touchscreen use is associated with poor sleep quality in infancy (Cheung et al, 2017 )—a likely important factor in the development of EF (Bernier et al, 2010 , 2013 )—as well as with poorer cognitive flexibility and parent‐reported effortful control at age 3.5 years (Portugal et al, 2020 ). Regular exposure (of any duration) to screen‐based media at 4 months is associated with poorer inhibitory control performance (but not cognitive flexibility or working memory) at 14 months (McHarg et al,).…”
Section: Introductionmentioning
confidence: 99%
“…Given this, the present study was the first to examine the relationship between screen time and the severity of ASD symptoms, before a toddler was formally diagnosed with ASD and before any standardized treatment intervention was implemented. Further, while previous research showed that background and foreground media have different effects among typically developing young children, such as reducing attention control [ 43 ], decreased inhibitory control [ 44 ], reduced cognitive flexibility [ 45 ], and decreased their ability to process verbal information [ 46 ], such fine-grained research on the association between background and foreground media and ASD among toddlers has received less attention so far. Note that the term ‘foreground programs’ refers to content specifically designed for children to actively draw their attention.…”
Section: Introductionmentioning
confidence: 99%